Voice therapy : clinical case studies - Stemple, Joseph C.; Hapner, Edie R. (Plural Publishing, Inc., 2019)
This book provides both the student and the working clinician with a broad sampling of management strategies as presented through clinical case studies by master voice clinicians, laryngologists, and other voice care professionals. Through concise patient histories, pre- and post-treatment evaluations, and tailored therapeutic approaches, this classic text addresses assessment, management, as well as treatment and therapy approaches for a range of voice disorders; muscle tension dysphonia, glottal incompetence and neurogenic disorders, and professional voice care.